Hyaluronidase allergy mimicking orbital cellulitis - Raichura, Nirav D.; Alam, Md Shahid; Jaichandran, V. V.; Mistry, Saurabh; Mukherjee, Bipasha (Orbit (Amsterdam), 2018)
Hyaluronidase enzyme is a common additive with local anesthetic agent to facilitate faster permeation of the anesthetic in periocular tissues during ophthalmic surgery. We report a series of five subjects presenting with clinical features mimicking orbital cellulitis following peribulbar anesthesia and consequently diagnosed with hyaluronidase hypersensitivity. The study was conducted at a tertiary eye care center in Southern India. It was a retrospective interventional case series. We retrospectively reviewed the case records of patients diagnosed as and treated for hyaluronidase allergy from 2011 to 2015. The presenting features included periocular edema, proptosis, and restriction of ocular movements. The symptoms appeared immediately after the injection to as late as 6 days after the surgery. All patients underwent comprehensive ophthalmic evaluation, relevant investigations, and dermal allergy tests. All five patients tested positive for hyaluronidase. Patients were treated with antihistaminics, systemic steroids, and emergency orbital decompression, when required. In majority of the patients, symptoms resolved in 3-5 days. Clinically, hyaluronidase allergy may mimic orbital cellulitis, which in the context of a recent intraocular surgery may be alarming for both the patient and the surgeon. However, with prompt intervention, the prognosis is extremely favorable in cases of hyaluronidase allergy. It is important for ophthalmic surgeons and anesthetists to recognize and differentiate this entity from the more serious vision threatening conditions.